Fetal head station during artificial rupture of membranes: a large retrospective cohort study - Sompolinsky, Yishai; Guedalia, Joshua; Vilk-Ayalon, Naama; Cohen, Sarah M.; Greenbaum, Shirley; Kabiri, Doron; Yagel, Simcha; Lipschuetz, Michal (Frontiers in Medicine, 2025)
IntroductionArtificial rupture of membranes (AROM) is a common intervention during delivery, usually done in order to expedite delivery. Studies to determine optimal timing of AROM according to cervical dilation were inconclusive. However, other important factors, which are known to be associated with timing of delivery were ignored. One of these factors is fetal head station (FHS). We sought to investigate the association between FHS during AROM and time to delivery and other obstetrical outcomes.Material and methodsA retrospective cohort study encompassing data from labors during a 12-year period were analyzed. All cases of singleton, term pregnancy with documented AROM time were included. The study population was stratified by parity.ResultsThis study cohort included 45,898 singleton, term vaginal delivery parturients with time stamp at time of AROM and delivery. Stratification by parity yielded 11,947 primiparas (26%) and 33,951 multiparas (74%). Across all sub-cohorts, as fetal head station decreased at AROM the duration from ROM to delivery was shorter. This trend seems to be stronger for multiparas than primiparas. Rates of cesarean delivery, postpartum hemorrhage, neonatal intensive care unit admission, and low 5-min Apgar scores were also negatively associated with decrease in fetal head station at AROM across all cervical dilations.ConclusionLower fetal head station at AROM is associated with shorter time to delivery as well as lower rates of cesarean delivery, postpartum hemorrhage, NICU admission, and 5-min Apgar ≤ 7. Fetal head station should be considered alongside cervical dilation during AROM. Our findings underscore the necessity for personalized timing of AROM, especially in multiparous women, to enhance maternal and neonatal health outcomes.